(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
With the advent of Sri Chaitanya, individuals and society found a better culture. Along with dancing, traveling, acting, literature also became his inseparable companion. In fact, Sri Chaitanya’s stream of love did not run towards any God outside the sphere of the concerned life, neglecting real life. His God resided in the individual, in society, and in life. Sri Chaitanya preached Bhaktiism not out of any deity but from a place of human tolerance and spiritual development. He played the role of social reformer. The wave of renaissance in literature came as if by the hand of consciousness. Sri Chaitanya was the pioneer of the changes that the modern age saw in the society of that time.